2023
DOI: 10.1002/tox.23871
|View full text |Cite
|
Sign up to set email alerts
|

Brexpiprazole suppresses cell proliferation and de novo lipogenesis through AMPK/SREBP1 pathway in colorectal cancer

Abstract: ObjectiveIn the present study, we investigated the role of brexpiprazole on cell proliferation and lipogenesis in colorectal cancer (CRC) and its molecular mechanism.MethodsThe effect of brexpiprazole on CRC cell proliferation was determined by CCK‐8, EdU assay, cell clone formation. The flow cytometry was evaluated cell cycle. Differential expression genes (DEGs) were identified by RNA‐seq assay after treating HCT116 cells with or without 20 μM brexpiprazole for 24 h. Then, the top 120 DEGs were analyzed by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(103 reference statements)
0
2
0
Order By: Relevance
“…In addition to their antipsychotic effects, the potential of antipsychotic medications to exhibit anticancer effects has been an ongoing area of research (5)(6)(7). While the current approval status from the U.S. Food and Drug Administration does not include use of any specific antipsychotic for cancer treatment, several studies have provided evidence that longterm use of antipsychotic medications may be associated with a decreased risk of certain cancers, including hepatocellular 1079 in vivo 38: 1079-1093 (2024) doi:10.21873/invivo.13542…”
Section: Control Group Safety Assessments Indicated Minimal Pathologi...mentioning
confidence: 99%
“…In addition to their antipsychotic effects, the potential of antipsychotic medications to exhibit anticancer effects has been an ongoing area of research (5)(6)(7). While the current approval status from the U.S. Food and Drug Administration does not include use of any specific antipsychotic for cancer treatment, several studies have provided evidence that longterm use of antipsychotic medications may be associated with a decreased risk of certain cancers, including hepatocellular 1079 in vivo 38: 1079-1093 (2024) doi:10.21873/invivo.13542…”
Section: Control Group Safety Assessments Indicated Minimal Pathologi...mentioning
confidence: 99%
“…It has recently been reported to function as an antitumour stem cell (CSCs), signi cantly inhibiting the growth of a wide range of tumour cells (lung cancer, pancreatic cancer, glioblastoma), decreasing the expression of Survivin, and reversing resistance to EGFR tyrosine kinase inhibitors, thus exerting anticancer effects [22][23][24] . Our group's pre-study has demonstrated that brexpiprazole can inhibit cell proliferation and lipid synthesis in CRC through the AMPK/SREBP1 signalling pathway [25] . However, whether brexpiprazole can also affect CRC EMT and inhibit its invasion and metastasis as well as the role of SREBP1 and Snail proteins family in it were not clearly understood.…”
Section: Introductionmentioning
confidence: 99%